Pemetaan Tutupan Lahan Di Desa Bukit Raya Kecamatan Tenggarong Seberang Menggunakan Citra Sentinel 2A - Agum Gumelar; Dyah Widyasasi; Suparjo; Dwi Agung Pramono; Nia Kurniadin (P2M Politeknik Pertanian Negeri Samarinda, 2022)
The purpose of this study was to make a land cover map and determine the condition of land cover in Bukit Raya Village, Tenggarong Seberang District.The method used in this study is the use of remote sensing Sentinel 2A for land cover mapping with a guided method using sample digitization on the screen for sampling in the land cover classification process. After using the supervised classification data obtained in the form of vector data that must be combined first before being used as a layout map.Results Based on the research, information was obtained about the process of making land cover maps in Bukit Raya Village, Tenggarong Seberang District and Land Cover Maps in Bukit Raya Village, Tenggarong Seberang District. The result of the area of ​​each land cover class is Agricultural Land with an area of ​​426.9 Ha,Air with an area of ​​138.2 Ha, Urban with an area of ​​176.1 Ha, Forest Land with an area of ​​391.7 Ha, Barren land with an area of ​​2 Ha, Industry 49.7 Ha, Transportation 59 Ha.